Level of Antenatal Care Services Utilization and Associated Factors Among Mothers who have Given Birth in the Past Twelve Months in Gelemso Town, West Hararghe Zone, Oromia National Regional State, East Ethiopia - Aboma Daniel; Egata Gudina; Ayalew Daniel (Journal of Women's Reproductive Health, 2020)
Background In Ethiopia, the levels of maternal and infant morbidity and mortality are among the highest in the world. This is attributed to, among other factors, none use of modern health care services by women. According to the 2011 Ethiopian Demographic Health Survey, more than seven in ten mothers did not receive antenatal care at all. Objectives The objective of this study was to determine level and identify factors influencing maternal antenatal care services utilization among mothers who gave birth in the last twelve months in Gelemso town west Hararghe Oromia, Ethiopia. Methods A community-based cross sectional study design was conducted on 347 study participants in Gelemso town west Hararghe Oromia Ethiopia from July 15, 2017 to August 15, 2017 G.C.A probability to proportional to size sampling technique was used to select the study population in two urban Kebeles. Data were collected using a pre tested structured questionairs. Descriptive results were presented using frequencies, and numerical summary measures. Bivariate analysis was carried out to assess the association between outcome variable and each in dependent variables. Odds ratio with 95% confidence level was estimated to identify factors associated with Antenatal Care (ANC) utilization using multivariable logistic regression. The statistical significance was declared at p- value < 0.05. Result The response rate this study was 98%. The prevalence of antenatal care service utilization was 64.6%. About 146 (42.1%) of the pregnant mother started antenatal care visit during the second trimester of pregnancy and a significant proportion 289(83.3%) had less than the recommended four visits. Educational status (AOR;15.19:CI 95%,6.006,38.417), husband attitude (AOR;1.995:CI 95%,1.016,3.916), marital status(AOR:4.587:CI 95%,1.888,11.146), planned pregnancy (AOR:4.938:CI 95%,2.514,9.702) were major factors associated with antenatal care service utilization. Conclusion Though more than half mother used antenatal care service in the study setting, two in ten of the mothers did not have the minimum number of visits recommended by World Health Organization. Promotion of information, education and communication in the community should be strengthened is to sustain antenatal care service utilization in the community.
Keywords: Antenatal care